2009
DOI: 10.1152/jn.00296.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sciatic Nerve Axotomy on Excitatory Synaptic Transmission in Rat Substantia Gelatinosa

Abstract: Effects of sciatic nerve axotomy on excitatory synaptic transmission in rat substantia gelatinosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 70 publications
4
43
0
1
Order By: Relevance
“…The remaining 16 pairs (9 inhibitory and 7 excitatory connections) were not included in this report, because of insufficient morphological and/or electrophysiological details. The electrophysiological features (RMPs, AP patterns, and AP frequency) of Gly, PKCγ + , and TC neurons sampled from both L4 and L5 spinal segments of SNL rats did not differ from those sampled from naive rats (P > 0.05; Supplemental Table 1), suggesting that nerve injury has little effect on the intrinsic excitability of Gly, PKCγ + , and TC neurons, which is consistent with previous studies (35,36). Thus, it is unlikely that mechanical allodynia in animals with SNL is a result of changes in membrane excitability or discharge pattern of these neurons.…”
Section: Paired Patch-clamp Recordings Identify Synaptic Connections supporting
confidence: 89%
“…The remaining 16 pairs (9 inhibitory and 7 excitatory connections) were not included in this report, because of insufficient morphological and/or electrophysiological details. The electrophysiological features (RMPs, AP patterns, and AP frequency) of Gly, PKCγ + , and TC neurons sampled from both L4 and L5 spinal segments of SNL rats did not differ from those sampled from naive rats (P > 0.05; Supplemental Table 1), suggesting that nerve injury has little effect on the intrinsic excitability of Gly, PKCγ + , and TC neurons, which is consistent with previous studies (35,36). Thus, it is unlikely that mechanical allodynia in animals with SNL is a result of changes in membrane excitability or discharge pattern of these neurons.…”
Section: Paired Patch-clamp Recordings Identify Synaptic Connections supporting
confidence: 89%
“…4A) and a decreased excitatory drive to putative inhibitory tonic-firing neurons ( Fig. 4B) (Bailey and Ribeiro-da-Silva, 2006;Balasubramanyan et al, 2006;Chen et al, 2009;Lu et al, 2009). Both of these changes would be expected to produce an overall increase in dorsal horn excitability.…”
Section: Increased Excitatory Drive To Excitatory Neurons and Decrmentioning
confidence: 99%
“…10 The excitability is associated with a series of synaptic plasticity such as long-term potentiation of spinal synaptic transmission, 36,37 which might be related to synthesis of more presynaptic vesicle protein, synaptophysin. 47 Several studies that used synaptophysin to quantify the number of terminals during neuroanatomical remodeling found that an increase within the ipsilateral dorsal horn of a CCI model highly correlated with the severity of neuropathic pain behaviors.…”
Section: Discussionmentioning
confidence: 99%